PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN TASAWUF UNTUK PENGUATAN KARAKTER SPIRITUAL SISWA DI ERA DIGITAL - Cahaya, Cahaya; Naldi, Anri; Nasutioan, Aqila Khairani (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to examine the use of Artificial Intelligence (AI) in Sufism learning and its contribution to strengthening students' spiritual character in the digital era. The background of this study is based on the challenges of Islamic education in providing relevant and engaging Sufism learning for a digital generation familiar with technology but experiencing a spiritual crisis. The research method used is a qualitative approach with a case study type. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation of AI-based Sufism practices in one modern Islamic school. The results show that AI is utilized in various forms, such as a spiritual guidance chatbot, an interactive dhikr application, and a visual-based learning platform for Sufism material. This utilization has been proven to be able to improve students' understanding of Sufi concepts, learning motivation, and emotional engagement in the learning process. However, AI cannot completely replace the role of teachers as spiritual guides who transmit Sufi values ​​through role models and direct guidance. Sufism learning supported by AI technology becomes a strategic tool to shape students' spiritual character, such as sincerity, patience, and closeness to Allah SWT, provided that its implementation is carried out contextually and valuable. Therefore, the use of AI needs to be synergized with a Sufi pedagogical approach based on spiritual experience, so that spiritual education maintains its meaning amidst the rapid flow of digitalization.